Study Guide : - Rush, Mark (Addison-Wesley, 1998)
Edition builds upon the tradition of leadership by sticking to 3 main goals: help the beginning student master the principles essential for understanding the economizing problem, specific economic issues, and the policy alternatives; help the student understand and apply the economic perspective and reason accurately and objectively about economic matters; and promote a lasting student interest in economics and the economy.